183k views
5 votes
Solve the following initial-value problem:

(ex+y)dx+(3+x+yey)dy=0, y(0)=1

0=

1 Answer

0 votes

Answer:


e^x+xy+3y+(y-1)e^y=4

Explanation:

Given that


(e^x+y)dx+(3+x+ye^y)dy=0

Here


M=e^x+y


N=3+x+ye^y

We know that

M dx + N dy=0 will be exact if


(\partial M)/(\partial y)=(\partial N)/(\partial x)

So


(\partial M)/(\partial y)=1


(\partial N)/(\partial x)=1

it means that this is a exact equation.


\int d\left(e^x+xy+3y+(y-1)e^y\right)=0

Noe by integrating above equation


e^x+xy+3y+(y-1)e^y=C

Given that

x= 0 then y= 1


e^0+0+3+(1-1)e^1=C

C=4

So the our final equation will be


e^x+xy+3y+(y-1)e^y=4

User Shafiq Jetha
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.